Dall'esilio all'abitare: Su «Der Waldgang» di Ernst Jünger (Balthazar, 2025)
This essay aims to interpret Ernst Jünger’s book Der Waldgang through the conceptual contraposition between exile and dwelling. It analyses the idea of Waldgang as an act of exile carried out by an individual in relation to the menaces produced by the power in the contemporary era, which exile individuals from their existence. The exile of the Waldgang is considered in its essential link to the «metaphysical power of humankind». The implications of the Waldgang for the human action and politics are taken into consideration to show how Jünger recognizes in it a way for the mankind to dwell anew in the world.
Keywords: Exile; Metaphysics; Ernst Jünger; Contemporary Freedom